Optimization of the Computer Laboratory in Supporting the Learning Process at SMP IBS Al-Hamra, Malang Regency - Ramadhani, Rifqi; Rofiq, Muhammad (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The aim of this research is to improve computer laboratory management in the context of education. The focus is on enhancing the efficiency and effectiveness of resource utilization and improving students' learning experiences in the computer laboratory environment. This research also aims to identify the challenges faced by the computer laboratory and develop strategies to improve the quality of learning, producing excellent and competitive competencies. Method: The method used in this study is a descriptive qualitative approach. The research techniques include observation and interviews to analyze user needs, evaluate infrastructure, and model sustainable management. Practical Applications: This research can provide insights for computer laboratory administrators, technicians, and educational managers. The recommended strategies can improve the accessibility and availability of computer resources, thereby enhancing students' learning experiences. Conclusion: By optimizing the management of computer laboratories, an approach focused on resource efficiency can create a dynamic learning environment. Through the identified practices, educational institutions can improve technology services and significantly support students' academic development.